The participation of Palestinian-Israeli politicians in public and commercial television and radio in Israel as capability. (March 2022) - Shomron, Baruch; Schejter, Amit
This study examines how media representations of Palestinian-Israeli politicians, can help community members realize their capabilities. The study's database is comprised of 1, 207 interviews conducted with Palestinian-Israeli politicians on news and current affairs programs on the three national television channels and the two national radio stations in Israel, for 24 months (2016-2017). We identified and analyzed the differences in the modes of representation between national and local Palestinian-Israeli politicians and between Palestinian-Israeli parliament members in the Joint List and Palestinian-Israeli parliament members in Zionist parties, all through the capabilities prism. In this study, we demonstrated how different types of Palestinian-Israeli politicians may potentially affect the realization of different political functions and capabilities. Analyzing political representations in the media through the theoretical framework of the 'capabilities approach' contributes to a more comprehensive insight into the roles the media can play promoting people's wellbeing and human rights, relative to traditional media theories.